2018
DOI: 10.1055/s-0038-1641715
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Ectoenzyme SmNPP5 from the Human Intravascular Parasite Schistosoma mansoni is an ADPase and a Potent Inhibitor of Platelet Aggregation

Abstract: Schistosomes are intravascular parasitic platyhelminthes infecting > 200 million people globally and causing a debilitating disease, schistosomiasis. Despite the relatively large size of the adult worms and their disruption of blood flow, surprisingly, they do not appear to provoke thrombus formation around them in vivo. We hypothesize that proteins expressed at the host-parasite interface are key to this ability. Here, we functionally express an ectonucleotide pyrophosphatase/phosphodiesterase homologue, SmNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…By recruiting host PLMG and promoting its conversion to plasmin, surface SmGAPDH could help drive the degradation of any blood clots forming around schistosomes in the vasculature thus allowing them unrestricted movement in vivo. This finding adds to our knowledge concerning the ability of schistosomes to control hemostasis: the worms have previously been reported to possess a series of ectoenzymes that likely impact blood clot formation by degrading host prothrombotic signaling molecules as well as key coagulation proteins (Elzoheiry et al, 2018b;Leontovyčet al, 2018;Mebius et al, 2013;Wang et al, 2018Wang et al, , 2017.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…By recruiting host PLMG and promoting its conversion to plasmin, surface SmGAPDH could help drive the degradation of any blood clots forming around schistosomes in the vasculature thus allowing them unrestricted movement in vivo. This finding adds to our knowledge concerning the ability of schistosomes to control hemostasis: the worms have previously been reported to possess a series of ectoenzymes that likely impact blood clot formation by degrading host prothrombotic signaling molecules as well as key coagulation proteins (Elzoheiry et al, 2018b;Leontovyčet al, 2018;Mebius et al, 2013;Wang et al, 2018Wang et al, , 2017.…”
Section: Discussionmentioning
confidence: 66%
“…Adults can live in the host bloodstream for many years and, despite being obstacles to blood flow, appear not to elicit damaging blood clot formation around them (Gryseels et al, 2006;Keating et al, 2006;Wang et al, 2017). Several mechanisms have been proposed by which schistosomes might inhibit blood clotting (Elzoheiry et al, 2019(Elzoheiry et al, , 2018bMebius et al, 2013;Wang et al, 2018Wang et al, , 2017. For instance, the worms possess a series of ectoenzymes that are thought to impact this process: the surface diphosphohydrolase SmATPDase1 and the surface phosphodiesterase/pyrophosphatase SmNPP5 can both cleave the platelet activator adenosine diphosphate (ADP) (Elzoheiry et al, 2018b), and, as shown for SmNPP5, this can block platelet aggregation in vitro (Elzoheiry et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This results in inhibition of ADP-mediated platelet activation and aggregation. [9][10][11] In this manner, the enzyme expressed at the tegumental surface helps to limit blood clot formation around the worms by acting as an anticoagulant and permit the parasites free movement within the vasculature. 11 Coagulation factors play a role in secondary hemostasis in conjugation with platelet and vascular endothelium.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, an S. mansoni tegumental adenosine triphosphate (ATP) diphosphohydrolase enzyme, SmATPDase1, can cleave the proinflammatory mediator ATP as well as adenosine diphosphate (ADP)—a powerful prothrombotic molecule . The worms possess an ectonucleotide pyrophosphatase/phosphodiesterase, SmNPP5, that can also cleave ADP and can impede platelet aggregation in vitro . Another schistosome tegumental ectoenzyme—the alkaline phosphatase SmAP—can degrade sphingosine‐1‐phosphate, a bioactive lipid that plays key roles in controlling inflammation and platelet aggregation .…”
Section: Introductionmentioning
confidence: 99%